Evaluation of Corneal Endothelium in Children and Adolescents with Type 1 Diabetes Mellitus - Urban, Beata; Raczyńska, Dorota; Bakunowicz-Łazarczyk, Alina; Raczyńska, Krystyna; Krętowska, Małgorzata (Mediators of Inflammation, 2013)
Purpose. To evaluate the systemic and local factors that contribute to the damage of endothelial cells in diabetic patients and to compare the endothelial structure of the cornea in diabetic and nondiabetic patients. Materials and Methods. The endothelial cell density (ECD) and central corneal thickness (CCT) were investigated in 123 eyes of type 1 diabetic patients and in 124 eyes of nondiabetic patients. The mean diabetic patients age was 15.34 ± 3.06 years versus 14.58 ± 2.01 years in the control group. The mean duration of diabetes was 8.02 ± 3.9 years. The corneal endothelium was imaged by the Topcon SP-2000P. Results. The mean ECD in diabetic eyes was 2435.55 ± 443.43 cells/mm2 and was significantly lower than in control group (2970.75 ± 270.1 cells/mm2). The mean CCT was 0.55 ± 0.03 mm in diabetic group versus 0.53 ± 0.033 mm in control group. ECD and CCT significantly correlated only with duration of diabetes. There was no correlation between ECD and CCT and patient age, sex, HbA1C level, and plasma creatinine level. Conclusions. ECD is decreased and CCT is increased in children and adolescents with diabetes mellitus. Duration of diabetes is the factor that affects ECD and CCT.